Legal Protection for Shopee Paylater Users Experiencing Bad Credit under Law Number 8 of 1999 concerning Consumer Protection. - Kurniasih, Dedeh (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this research is to find and deeply analyze the legal protection for Shopee Paylater users experiencing bad credit under Law Number 8 of 1999 concerning Consumer Protection and the resolution of Shopee Paylater bad credit disputes through Online Dispute Resolution (ODR). The approach method in this research is a normative juridical approach. The data sources consist of primary data supported by secondary data. The primary legal data collection technique used a research instrument in the form of document studies and recording. The results of this research show that Article 1 Number 1 of Law Number 8 of 1999 concerning Consumer Protection aims to provide security in the form of protection for consumers when there are unfair conditions that affect the consumer. Furthermore, the resolution of Shopee Paylater bad credit disputes through Online Dispute Resolution (ODR) is the most appropriate alternative dispute resolution method for Shopee Paylater problems because it is more efficient and not hindered by geographical conditions.